Facies and Sequence Stratigraphy Analysis of Carbonate Formation in “ANDRI” Field, Offshore Indonesian Basin: Impacts on Reservoir and Hydrocarbon Quality - Muhammad Said Harfiandri; Budhi Setiawan; Yogie Zulkurnia Rochmana; Riezal Arieffiandhany (Department of Geophysical Engineering, Faculty of Engineering, University of Lampung, 2025)
The Baturaja Formation in the northern West Java Basin is the focus of many oil and gas exploration and production activities, mainly due to its significant reservoir potential. The formation consists of Early Miocene-aged carbonate sedimentary layers with good hydrocarbon reservoir characteristics, distribution, and quality. This study aims to identify the reservoir characteristics and hydrocarbon prospective zones of carbonate formation through integrated facies analysis, sequence stratigraphy, diagenetic processes, and petrophysical evaluation. This research uses qualitative and quantitative methods, where the qualitative stage starts with lithological interpretation from core data and thin sections of rock. Furthermore, quantitative analysis is carried out to calculate reservoir properties based on petrophysical analysis such as shale volume, porosity, permeability, and water saturation. The results show that the shoal reef facies exhibit higher hydrocarbon potential than the lagoonal facies, with greater maximum hydrocarbon thickness and more consistent hydrocarbon distribution. This follow the characteristics of the shoal reef facies, which have grain supported characteristics with low clay matrix content, a high degree of pore connectivity and high permeability Diagenetic process also plays an important role in the formation of porosity and permeability, where the shoal reef facies with fossiliferous packstone lithofacies exhibit good porosity and permeability, such as intercrystalline, intraparticle, and fracture porosity.This is due to the depositional process of the facies in a high-energy environment with abundant carbonate production growth rate.